2023
DOI: 10.1097/shk.0000000000002109
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Angiotensin Ii as Primary Vasopressor in Critically Ill Adults With Vasodilatory Hypotension: The Aramis Study

Abstract: The aim of the study is to evaluate the efficacy and safety of using angiotensin II (Ang2) as primary vasopressor for vasodilatory hypotension. Methods: This was a prospective observational study of critically ill adults admitted to an academic intensive care unit (ICU) with vasodilatory hypotension. We treated 40 patients with Ang2 as primary vasopressor and compared them with 80 matched controls who received conventional vasopressors (norepinephrine, vasopressin, metaraminol, epinephrine, or combinations). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…There was no difference in the primary outcome regarding peak serum creatinine levels. However, in a subgroup analysis of this study, an effect of angiotensin II on peak serum creatinine levels was found in patients who had previously been exposed to RAS inhibitors before admission, suggesting the need for targeted investigation of this population in future randomized controlled trials [28].…”
Section: Canonical Renin-angiotensin System In Sepsis-associated Acut...mentioning
confidence: 64%
“…There was no difference in the primary outcome regarding peak serum creatinine levels. However, in a subgroup analysis of this study, an effect of angiotensin II on peak serum creatinine levels was found in patients who had previously been exposed to RAS inhibitors before admission, suggesting the need for targeted investigation of this population in future randomized controlled trials [28].…”
Section: Canonical Renin-angiotensin System In Sepsis-associated Acut...mentioning
confidence: 64%
“…Though substantial observational data on the use of AT2 in real-world practice and the significance of renin and DPP3 are accumulating, the prospective interventional nature of the DARK-Sepsis trial and the inclusion of a control arm for comparison will allow us to specifically dissect whether these biomarkers serve as general prognostic markers in sepsis or if, as we hypothesize, they can be used specifically to predict response to AT2. While the use of an RCT design for such a mechanistic study is less common, our study design — in which patients in both arms are treated with FDA-approved agents for their approved indications — allows us to generate randomized data with limited additional risk (beyond the substantial risk inherent in the treatment of septic shock with vasopressor therapy), especially considering the emerging data that AT2 is safe when used as a first-line vasopressor therapy in vasodilatory shock [ 27 ]. In addition, though randomization will mitigate between-group differences in severity of illness, adjustment for severity of illness is vital in interpreting within-group assessments of the ability of these biomarkers to predict vasopressor response.…”
Section: Discussionmentioning
confidence: 99%
“…To determine if the ability of biomarker levels to predict clinical response to vasopressor therapy is specific to AT2, we will assess biomarker levels in patients with septic shock treated with AT2 and in a control group not treated with AT2. Because we hypothesize that biomarker levels will identify patients that specifically benefit from AT2 and because the need for high-dose catecholamine monotherapy in septic shock is consistently associated with mortality [ 26 ], we will introduce AT2 therapy earlier in the course of illness than in ATHOS-3, an approach that appears safe based on recent pilot trial data [ 27 ] and potentially beneficial based on additional post hoc analyses of ATHOS-3 data [ 28 ]. To shed light on the relationship between AT2 response, overall outcome, biomarker levels, and changes in biomarker levels, we will collect biomarker levels at multiple time points in patients treated with AT2 and controls.…”
Section: Study Aims and Objectivesmentioning
confidence: 99%
“…Notably, though the vast majority of studies of angiotensin II have employed it as a second- or third-line agent, two recent pilot studies reported that angiotensin II as first-line vasopressor may be safe and effective [ 49 , 50 ]. A further prospective observational study of 40 patients with vasodilatory shock treated initially with angiotensin II compared to 80 matched controls found that angiotensin II was associated with lower ICU mortality and lower rates of troponin elevation, though no adjustment was made for multiple comparisons and no benefit was found in the primary study outcome of peak serum creatinine [ 49 ]. Clearly, additional data on the use of angiotensin II as a first-line vasopressor are needed.…”
Section: Angiotensin II Therapy: Clinical Evidencementioning
confidence: 99%
“…This observation is consistent with preclinical data suggesting that angiotensin II may be prothrombotic [ 67 , 68 ]. However, the clinical significance of these observations remains unclear: while a meta-analysis of > 1,700 critically ill patients unexposed to angiotensin II reported a deep vein thrombosis (DVT) rate of 12.7% [ 69 ], subsequent observational studies of angiotensin II use reported rates of DVT of ≤ 5% [ 49 , 52 , 70 ]. Nonetheless, pharmacologic DVT prophylaxis is prudent in patients treated with angiotensin II whenever possible.…”
Section: Angiotensin II Therapy: Safetymentioning
confidence: 99%